Efficient side near surface mounting techniques for strengthening of reinforced concrete beams / Md Akter Hosen - Md Akter , Hosen (2019)
Reinforced concrete (RC) structures require rehabilitation or strengthening due to increased live load, repair of damaged structural elements, modification of existing structure and improvement of the structural system, prolong design life, or errors in design and construction. Currently, the most common strengthening methods that are being used in the construction industry are externally bonded reinforcement (EBR) and near surface mounted (NSM) techniques. However, both techniques have limitations in their application and to overcome these, a new approach is presented in this study. This main objective of this research is to investigate the effect of placing the strengthening materials at the side of the beams for enhancing flexural performance and improve failure modes. Different methods, namely side near surface mounted (SNSM), side externally bonded reinforcement (S-EBR) and side hybrid (SH) techniques were employed in this research. The structural performance of RC beams strengthened with SNSM, S-EBR and SH techniques using fiber reinforced polymer (FRP) was investigated. In addition, instead of using conventional epoxy, normal and palm oil fuel ash mortars were used for replacement for epoxy adhesive; further, pre-cracked lightweight beams strengthened with S-EBR technique was investigated. Analytical models were used to predict the flexural responses of the tested strengthened RC beams in this research. Sixty-five RC beams were fabricated for the experimental programme and these were divided into six groups. The strengthening materials comprised of GFRP bars, CFRP bars, plate and fabrics. All RC beams were tested under four-point bending using the Instron Universal testing machine and the results were recorded in a TML data logger. The experimental test results showed that strengthening with SNSM technique utilising GFRP bars significantly enhanced the first cracking and ultimate loads, energy absorption capacity, ductility and stiffness specimens. Effect of the bond length is more significant on the flexural performance compared with the amount of strengthening reinforcement. Epoxy substituted by sustainable palm oil fuel ash (POFA) mortar had a superior flexural performance in comparison with the normal mortar in SNSM-GFRP bars strengthened specimens. SNSM-CFRP strips strengthening technique considerably enhanced the first cracking, yield, and ultimate load capacities up to 153%, 108%, and 147%, respectively; further, ductility, stiffness, and energy absorption characteristics improved prominently. SNSM technique with vertically oriented strips has shown better flexural responses compared with the horizontally oriented strips. In S-EBR technique, an increase in the tensile reinforcement ratio and width of the CFRP laminates significantly enhanced the load carrying capacity, energy absorption capacity, stiffness and ductile response of the normal and lightweight pre-cracked strengthened beams, respectively. The SH technique with or without end-anchorage, and varying bond length of the strengthened reinforcements significantly increased the flexural responses of the beams. Increase in the number of strips in the SNSM grooves and width of plates in the S-EBR with or without end-anchorage remarkably enhanced the structural performance of the beams by SH technique. Overall, the analytical models predicted the experimental results reasonably well.